Patterns of Allergic Sensitization and Factors Associated With Emergence of Sensitization in the Rural Tropics Early in the Life Course: Findings of an Ecuadorian Birth Cohort - Cooper, Philip J.; Chis Ster, Irina; Chico, Martha E.; Vaca, Maritza; Barreto, Mauricio L.; Strachan, David P. (Frontiers in Allergy, 2021)
Introduction: There are limited data on emergence of allergic sensitization (or atopy) during childhood in tropical regions. Methods: We followed a birth cohort of 2404 newborns to 8 years in tropical Ecuador and collected: risk factor data by maternal questionnaires periodically from birth; atopy was measured by skin prick test reactivity (SPT) to aeroallergens in parents, and aeroallergens and food allergens in children at 2, 3, 5, and 8 years; and stool samples for soil-transmitted helminths (STH) from children periodically to 8 years and from parents and household members at the time of recruitment of cohort children. Data on risk factors were measured either at birth or repeatedly (time-varying) from birth to 8 years. Longitudinal repeated-measures analyses were done using generalized estimating equations to estimate an the age-dependent risk of positive SPT (SPT+) to any allergen or mite during early childhood to school age. Results: SPT+ to any allergen was present in 29.0% of fathers and 24.8% of mothers, and in cohort children increased with age, initially to mite but later to cockroach, reaching 14.8% to any allergen (10.7% mite and 5.3% cockroach) at 8 years. Maternal SPT+, particularly presence of polysensitization (OR 2.04, 95% CI 1.49-2.77) significantly increased the risk of SPT+ during childhood, while household overcrowding at birth decreased the risk (OR 0.84, 95% CI 0.72-0.98). For mite sensitization, maternal polysensitization increased (OR 2.14, 95% CI 1.40-3.27) but rural residence (OR 0.69, 95% CI 0.50-0.94) and birth order (3rd -4th vs. 1st – 2nd: OR 0.71, 95% CI 0.52-0.98) decreased the risk. Time-varying exposures to agricultural activities (OR 0.77, 95% CI 0.60-0.98) and STH parasites (OR 0.70, 95% CI 0.64-0.91) during childhood decreased while anthelmintics increased the childhood risk (OR 1.47, 95% CI 1.05-2.05) of mite sensitization. Conclusion: Our data showed the emergence of allergic sensitization, primarily to mite and cockroach allergens, during childhood in tropical Ecuador. A role for both antenatal and postnatal factors acting as potential determinants of SPT+ emergence was observed.